Optimalisasi Daya Dukung Tanah Lempung dengan Campuran Spent Bleaching Earth (SBE) dan Kapur Tohor - Alwiah, Sy Sarah; Anggreana, Vella; Ahmadi, Heri; Suftri, Frisca Amelia (Universitas Ibn Khaldun, 2026)
Clay soil has high water content, high plasticity, and low bearing capacity, which often causes structural problems in construction projects, as observed at the research location on Jl. Siak II, Masjid Raya Province of Riau area, where structural settlement occurred due to insufficient soil bearing capacity. This study aims to improve the physical properties and bearing capacity of clay soil through stabilization using a mixture of Spent Bleaching Earth (SBE) and quicklime. Laboratory tests were performed using a mixture variation of 22.5% SBE and 25% quicklime with curing durations of 0, 4, and 7 days and a soaking period of 4 days. The laboratory program included water content, specific gravity, sieve analysis, Standard Proctor compaction, and California Bearing Ratio (CBR) tests. The untreated soil exhibited a water content of 29.45%, a specific gravity of 2.43 g/cm³, 40.44% retained on sieve No.200, and a maximum dry density of 1.57 kN/m³ at an optimum moisture content of 20.8%. The CBR value of the untreated soil increased with curing time, reaching 13.99% on the 7th day. For the stabilized soil, the highest CBR improvement was achieved by the mixture of soil + SBE + quicklime with 7 days of curing, reaching 29.36%, while the best CBR under 4-day soaking occurred in the mixture of soil + quicklime with a CBR value of 20.75%. These findings indicate that the combined use of SBE and quicklime is effective in enhancing the bearing capacity of clay soil, with optimal performance observed after 7 days of curing.